Reviewing the Concept of Enterprise Content Management (ECM)- - Mohamad Rahimi Mohamad Rosman (Journal of Digital Information Management, 2020)
Content is simply information that is put to use through the process of repackaging and is then published for a specific purpose (i.e. text, image, 3D data, video, etc.). Organisations deal with various information assets, also known as ‘content’, to run their business operations and make important decisions. Managing content is always a challenge for an organisation. More content, particularly in digital form, that goes beyond the control of organisations is being produced. Enterprise Content Management (ECM) was initiated to help organisations manage their information assets. Over a period of 25 years, ECM has intermittently been the focus of attention due to difficulties in setting a solid research framework and the vagueness of the term ECM. Therefore, this research aims to provide a comprehensive analysis of the ECM literature to identify the current state of knowledge and future research directions. An ECM research framework is proposed to guide the literature review analysis. Based on the analysis, several important observations are highlighted and practical implications for further research are proposed.